Lifestyles of Spanish university students during the 2020 COVID-19 lockdown - Fernando García del Castillo López; Juan Tortosa Martínez; Irene Ramos Soler; Jose Antonio García del Castillo Rodríguez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
During the 2020 stay-at-home lockdown ordered as a response to the COVID-19 pandemic, university students had access to diverse digital technologies, which offered researchers the opportunity to study changes in their lifestyles while they occurred and to classify them into groups according to such lifestyles. Therefore, the main objective of this research is to establish a typology of university students according to the lifestyles they followed during the lockdown, based on the study of their daily routines, emotional state, media consumption habits and use of apps. The study is based on a sample of 913 Spanish university students. Data has been processed with SPSS 28.0 and SPAD 5.0. The following six groups were identified by using factor analysis and multiple correspondence analysis: 1) the fearless and adapted (21%); 2) the unhealthy (22.56%); 3) the hardworking and studious (27.93%); 4) the hyperconnected (9.09%); 5) the sedentary and withdrawn (13.85%); and 6) the athletic and healthy (6.68%). The use of apps for social relations is shown as a relevant construct, in relation to other indicators such as emotional state, time spent on studies, leisure, family and physical activity. The lifestyles observed exhibit differences with respect to sports activity, eating habits and rest routines, as well as time spent on academic and professional activities.